From Coast To Hinterlands: The Spread Of Islam In Sumatra - Gabriel Siburian; Geryl Valeri Evans; Doan Juan Panjaitan; Levirisky Siahaan; Muhammad Nur Hidayat; Pristi Suhendro Lukitoyo (Journal Of Global Research Publications, 2026)
The spread of Islam on Sumatra Island originated in coastal regions before expanding into the hinterlands. Utilizing a historical approach, this study reveals that maritime trade routes served as the gateway for traders and missionaries from Arabia, Persia, and Gujarat to engage in commerce and dawah across Sumatra. Islam initially flourished in Barus, Samudera Pasai, and Aceh before eventually expanding into the interior through river networks, intermarriage, and the political influence of the sultanates. The findings of this study indicate that the process of Islamization in Sumatra was not uniform; in coastal areas, Islam tended to be more Cosmopolitan, whereas in the interior, cultural acculturation with local traditions occurred. The success of this expansion marked the starting point of a religious transformation across the Indonesian archipelago